1989
DOI: 10.1016/0304-3959(89)90077-8
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic facilitation of sustained discharges of polymodal nociceptors

Abstract: Injection of a compound algogenic substance into a receptive field of the skin induced sustained discharges from single polymodal nociceptors (PMNs) in rats. Stimulation of the sympathetic nerve (SS) innervating the receptive field obviously increased the sustained discharges. Some units were first facilitated and then inhibited. The sympathetic effect could be activated repeatedly and lasted a long time. Injection of norepinephrine (NE, 5 micrograms) into the local artery caused a similar effect. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(35 citation statements)
references
References 14 publications
1
33
0
1
Order By: Relevance
“…Additional studies are also required to elucidate the role of peripheral versus central β 2/3 -adrenergic systems in the development of COMT-dependent pain sensitivity. Although epinephrine and norepinephrine have previously been shown to sensitize nociceptors located on small diameter primary afferents in the periphery (Hu and Zhu 1989;Khasar et al 1999b;Shyu et al 1989), elevated levels of central catecholamines are generally associated with descending inhibition of pain via actions at α 2 ARs or D 2 DARs in the spinal dorsal horn (Millan 2002). Antidepressants used extensively in the treatment of persistent pain conditions, are thought to inhibit pain transmission at the spinal level by increasing synaptic levels of norepinephrine and serotonin (Sanchez and Hyttel 1999) as well as by blocking tetrodotoxin-resistant sodium channels (Brau et al 2001).…”
Section: Comt Inhibition Increases Pain Behavior Via β 2 and β 3 Adrementioning
confidence: 99%
“…Additional studies are also required to elucidate the role of peripheral versus central β 2/3 -adrenergic systems in the development of COMT-dependent pain sensitivity. Although epinephrine and norepinephrine have previously been shown to sensitize nociceptors located on small diameter primary afferents in the periphery (Hu and Zhu 1989;Khasar et al 1999b;Shyu et al 1989), elevated levels of central catecholamines are generally associated with descending inhibition of pain via actions at α 2 ARs or D 2 DARs in the spinal dorsal horn (Millan 2002). Antidepressants used extensively in the treatment of persistent pain conditions, are thought to inhibit pain transmission at the spinal level by increasing synaptic levels of norepinephrine and serotonin (Sanchez and Hyttel 1999) as well as by blocking tetrodotoxin-resistant sodium channels (Brau et al 2001).…”
Section: Comt Inhibition Increases Pain Behavior Via β 2 and β 3 Adrementioning
confidence: 99%
“…2 m/s were classified as C fibers [23,24] . If the amplitude and shape of the action potentials remained the same during the recordings, they were defined as responses from a single C fiber; sometimes collision tests were also used (see below) [24] . Only these single C fibers were studied further.…”
Section: In Vivo Electrophysiological Recording Of Single C Fiber Dismentioning
confidence: 99%
“…Action potentials were amplified (VC-11, Nihon Kohden) and recorded via a computer A/D board with a signal sampling rate of 10 kHz. The C-fiber was identified as a polymodal nociceptor when C-fiber firings in the receptive field were evoked by 100 g Von Frey hair as well as a small cotton ball with hot water (55-60°C) (Hu and Zhu 1989). In the present study, all of the C-fibers reported were polymodal nociceptive only.…”
Section: Animal Model Of Diabetic Neuropathic Pain and Behavioral Testsmentioning
confidence: 46%